Three-Phase Power Flow Calculations Using Initial Voltage Estimation Method for Unbalanced Distribution Networks - Nien-Che Yang; Meng-Jia Liu; Kai-You Lai; Eunike Widya Adinda (IEEE Access, 2022)
In this study, we propose a three-phase power-flow calculation using the initial voltage estimation for unbalanced radial distribution systems. Graph theory, Kron reduction, and injection current methods are combined in the proposed method. Network components, such as transmission lines, transformers, and loads, are integrated into the system bus impedance matrix ( $Z_{BUS}$ ). If there are only network components with constant or quasi-constant impedance characteristics in distribution systems, the power flow can be solved without iterative procedures. Therefore, the proposed method can be called the “direct solution method”. Because the initial estimations can approximate the final converged solutions, the proposed method has excellent convergence capability. To demonstrate the feasibility and effectiveness of the proposed method, five IEEE test systems are used for comparisons in different scenarios. The test results demonstrate that the proposed method performs well by offering good convergence in complex distribution networks with different transformer connections.